A qualitative investigation of specialist orthodontists in New Zealand. Part 1. Orthodontists and orthodontic practice - Soma Kieran J.; Murray Thomson W.; Morgaine Kate C.; Harding Winifred J. (Sciendo, 2012)
Background: Current knowledge of orthodontic practice is largely anecdotal and the lack of systematic knowledge can create barriers to better identifying the factors that make a successful orthodontist. The aim of this study was to investigate the routine practising lives of New Zealand orthodontists in order to generate an understanding of the reality of orthodontic specialist practice and its effects on their professional and personal lives.